Annual review of working conditions in the EU 2008-2009 - Giaccone, Mario; Colleoni, Elanor; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2009)
The sixth annual review of the European Working Conditions Observatory (EWCO), which is part of the European Foundation for the Improvement of Living and Working Conditions (Eurofound), summarises the main developments at EU level in the area of working conditions and quality of work and employment during the period February 2008 to January 2009. Divided into five thematic chapters, it explores labour market developments and demographic change, social protection, flexicurity and corporate social responsibility (CSR), working conditions, and equal opportunities.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Labor supply -- European Union countries; Electronic books